Proteomics in cancer research. Issue 5 (1st August 2002) - Wu, W.; Hu, W.; Kavanagh, J. J.
Abstract : With the human genome sequence now determined, the field of molecular medicine is moving beyond genomics to proteomics. In the field of cancer research, the key question is: how can oncologists best use techniques of proteomics in basic research and clinical application? In the postgenomic era, proteomics promises the discovery of biomarkers and tumor markers for early detection and diagnosis, novel protein-based drug targets for anticancer therapy, and new endpoints for the assessment of therapeutic efficacy and toxicity. This review paper will explore key themes in proteomics and their application in clinical cancer research.